A Sociopragmatic Analysis On The Summons And Speech Interruption Expression In The Tragedy Of Hamlet, Prince Of Denmark - Hidayanto, Rahmad (2004)
This research is focusing on summons and interruption expression used by the characters on "The Tragedy of Hamlet, Prince of Denmark". The objectives of the study are to describe the language forms, to clarify the uses, and to examine the intention of summons and interruption in the film text. This research is included in qualitative type. In this case, the writer uses documentation method to collect the data. To clarify the form, the writer refers to the linguistic form, to clarify the reason, the writer employees Hymes SPEAKING formula and to clarify the intentions, the writer uses speech act theory. The result of the study shows view form. There are one lexical categori of word, namely noun, and five noun phrases. They are noun-noun phrase, determiner-noun phrases, determiner-degree-adjective-noun phrase, determiner- adjective noun and adjective-noun phrase, and three types of sentence, namely: imperative, interrogative and declarative. There are three reasons of the uses, they are: (1) to show intimacy, (2) to show close relationship, (3) to show respect and, (4) to show power. There writer finds two intentions of the uses, they are for opening conversation and for asking for help.